Microbial Community Analysis in Sichuan South-road Dark Tea Piled Center at Pile-Fermentation Metaphase and Insight Into Organoleptic Quality Development Mediated by Aspergillus niger M10 - Zou, Yao; Zhang, Ying; Tian, Yun; Liu, Minqiang; Yuan, Yue; Lai, Yuqing; Liu, Xuyi; Xu, Wei; Tan, Liqiang; Tang, Qian; Li, Pinwu; Xu, Jingyi (Frontiers in Microbiology, 2022)
Microbes are critical in the South-road Dark Tea (SSDT) organoleptic quality development during pile-fermentation. Piled tea center at fermenting metaphase is crucial for the conversion of its quality components. In this study, we investigated the microbial community of piled SSDT center below the stacked tea surface of 15 cm (SSDTB), 50 cm (SSDTX), and 85 cm (SSDTH) on the second turning time of pile-fermentation, respectively. Results showed that SSDTH and SSDTB had a higher similarity in microbial community. Pantoea (36.8%), Klebsiella (67.7%), and Aspergillus (35.3%) were the most abundant in SSDTH, SSDTB, and SSDTX respectively. We found 895 species were common among all samples, but 86, 293, and 36 species were unique to SSDTB, SSDTX, and SSDTH respectively. Aspergillus niger showed high co-occurrence and was positively correlated with numerous microbes in SSDT samples, and Aspergillus niger M10 isolated from SSDTX was excellent at enhancing soluble sugar (SS), amino acids (AA), theaflavin (TF), and thearubigins (TR) contents, while decreasing catechin (Cat), TPs/AA, Caf/SS, Cat/SS, TPs/SS, and (TPs+Caf)/SS levels in AM10 post fermentation, as compared with the control. Moreover, it also produced a noticeable difference in the CIELab parameters in dried, liquor, and infused tea colors between AM10 and control during fermentation. When it was further inoculated on differential mediums, we detected glycoside hydrolases including β-glucosidase, mannosidase, pectinase, cellulase, amylase, and α-galactosidase being secreted by Aspergillus niger M10. Taken together, SSDXT presented a more unique microbial community. Aspergillus niger M10 probably improved the sweet and mellow taste, and the yellow brightness and red color of SSDT during fermentation. It also provided new insights into the microbial profile and organoleptic quality development mechanism of SSDT during pile-fermentation.